Rebuilding Arab Defense : US security cooperation in the Middle East - Saab, Bilal Y., 1980- (United Kingdom: Lynne Rienner Publishers, 2022)
"Explores the current state of US security cooperation in the Middle East, considering why the military capabilities of US allies in the region are still lacking and suggesting avenues for effective change"--
The US-Arab Security Partnership -- US Military Assistance: Old Vs. New Model -- Saudi Arabia: Rebuilding Everything -- Jordan: Still Falling Short -- Lebanon: Working Against All Odds -- The United Arab Emirates: Breaking New Ground -- Cultural and Structural Challenges -- Achieving Security Cooperation.
Includes bibliographical references (pages 217-237) and index.
Keywords: National security -- Middle East; Middle East -- Defenses; Middle East -- Armed Forces -- Forecasting; United States -- Military relations -- Middle East; Middle East -- Military relations -- United States; Middle East -- Military policy -- 21st century; United States -- Military policy -- 21st century